A modern view of the problem of treatment of cicatricial stenoses of the trachea - V.V. Boyko; V.V. Kritsak; A.L. Sochnieva; V.V. Tkachenko; O.M. Tishchenko (Medicine Today and Tomorrow, 2024)
Ezemba N, Echieh CP, Chime EN, Okorie CO, Okonna FG, Idoko FL, Arua OA. Postintubation tracheal stenosis: Surgical management. Niger J Clin Pract. 2019;22:134-7. DOI: 10.4103/njcp.njcp_288_18. PMID: 3066603. Lale Az, Oz B, Akcan AC, Sozuer EM, Arıkan TB, Gok M. Determination of risk factors causing hypocalcaemia after thyroid surgery. Asian J Surg. 2019;42(9):883-9. DOI: 10.1016/j.asjsur.2018.12.009. PMID: 30685145. Du C, Ma L, Chai N, Gao Y, Niu X, Zhai Y, et al. Factors affecting the effectiveness and safety of submucosal tunneling endoscopic resection for esophageal submucosal tumors originating from the muscularis propria layer. Surg Endosc. 2018;32(3):1255-64. DOI: 10.1007/s00464-017-5800-x. PMID: 28842802. Al-Hilli Z, Strajina V, McKenzie TJ, Thompson GB, Farley DR, Regina Castro M, et al. Thyroglobulin Measurement in Fine-Needle Aspiration Improves the Diagnosis of Cervical Lymph Node Metastases in Papillary Thyroid Carcinoma. Ann Surg Oncol. 2017;24(3):739-44. DOI: 10.1245/s10434-016-5625-1. PMID: 27738849. Ali SZ, Cibas ES. The Bethesda System for Reporting Thyroid Cytopathology: Definitions, Criteria, and Explanatory Notes. 2nd ed. New York: Springer; 2018. DOI: 10.1007/978-3-319-60570-8. Aresta G, Jacobs C, Araujo T, Cunha A, Ramos I, Ginneken B, Campilho A. iW-Net: an automatic and minimalistic interactive lung nodule segmentation deep network. Pre-print 2018. DOI: 10.48550/arXiv.1811.12789. Alexander EK, Pearce EN, Brent GA, Brown RS, Chen H, Dosiou C, et al. 2017 Guidelines of the American Thyroid Association for the Diagnosis and Management of Thyroid Disease During Pregnancy and the Postpartum. Thyroid. 2017;27(3):315-89. DOI: 10.1089/thy.2016.0457. Erratum in: Thyroid. 2017;27(9):1212. DOI: 10.1089/thy.2016.0457.correx. PMID: 28056690. Kann BH, Thompson R, Thomas CR Jr, Dicker A, Aneja S. Artificial Intelligence in Oncology: Current Applications and Future Directions. Oncology (Williston Park). 2019;33(2):46-53. PMID: 30784028. Palaniappan S, Shanmughavelu L, Prasad HK, Subramaniam S, Krishnamoorthy N, Lakkappa L. Improving iodine nutritional status and increasing prevalence of autoimmune thyroiditis in children. Indian J Endocrinol Metab. 2017;21(1):85-9. DOI: 10.4103/2230-8210.195996. PMID: 28217504. Liua X, Houb F, Qinc H, Hao A. Multi-view Multi-scale CNNs for Lung Nodule Type Classification from CT Images. Pattern Recognition 2018;77:262-75. DOI: 10.1016/j.patcog.2017.12.022. Russ G, Bonnema SJ, Erdogan MF, Durante C, Ngu R, Leenhardt L. European Thyroid Association Guidelines for Ultrasound Malignancy Risk Stratification of Thyroid Nodules in Adults: The EU-TIRADS. Eur Thyroid J. 2017;6(5):225-37. DOI: 10.1159/000478927. PMID: 29167761. Sleptsov I, Chernikov R, Pushkaruk A, Sablin I, Tilloev T, Timofeeva N, Knyazeva P. Tension-free thyroidectomy (TFT): initial report. Updates Surg. 2022;74(6):1953-60. DOI: 10.1007/s13304-022-01338-x. PMID: 35913529. Steward DL, Carty SE, Sippel RS, Yang SP, Sosa JA, Sipos JA, et al. Performance of a multigene genomic classifer in thyroid nodules with indeterminate cytology: A Prospective Blinded Multicenter Study JAMA Oncol. 2019;5(2):204-12. DOI: 10.1001/jamaoncol.2018.4616. PMID: 30419129. Boutzios G, Tsourouflis G, Garoufalia Z, Alexandraki K, Kouraklis G. Long-term sequelae of the less than total thyroidectomy procedures for benign thyroid nodular disease. Endocrine. 2019;63(2):247-51. DOI: 10.1007/s12020-018-1778-y. PMID: 30302663. Xiong XF, Xu L, Fan LL, Cheng DY, Zheng BX. Long-term follow-up of self-expandable metallic stents in benign tracheobronchial stenosis: a retrospective study. BMC Pulm Med. 2019;19(1):33. DOI: 10.1186/s12890-019-0793-y. PMID: 30736856. Villarroya-Marquina I, Lorente-Poch L, Sancho J, Sitges-Serra A. Influence of gender and women's age on the prevalence of parathyroid failure after total thyroidectomy for multinodular goiter. Gland Surg. 2020;9(2):245-51. DOI: 10.21037/gs.2020.02.01. PMID: 32420248. Li Y, Jin C, Li J, Tong M, Wang M, Huang J, et al. Prevalence of Thyroid Nodules in China: A Health Examination Cohort-Based Study. Front Endocrinol (Lausanne). 2021;12:676144. DOI: 10.3389/fendo.2021.676144. PMID: 34122350. Zuo T, Gao Z, Chen Z, Wen B, Chen B, Zhang Z. Surgical Management of 48 Patients with Retrosternal Goiter and Tracheal Stenosis: A Retrospective Clinical Study from a Single Surgical Center. Med Sci Monit. 2022;28:e936637. DOI: 10.12659/MSM.936637. PMID: 35949114. Hakiri S, Fukui T, Mori S, Kawaguchi K, Nakamura S, Ozeki N, et al. Clinicopathologic Features of Thymoma With the Expression of Programmed Death Ligand 1. Ann Thorac Surg. 2019;107(2):418-24. DOI: 10.1016/j.athoracsur.2018.08.037. PMID: 30312607. Dobnig H, Amrein K. Value of monopolar and bipolar radiofrequency ablation for the treatment of benign thyroid nodules. Best Pract Res Clin Endocrinol Metab. 2019;33(4):101283. DOI: 10.1016/j.beem.2019.05.007. PMID: 31278063. Titov S, Demenkov PS, Lukyanov SA, Sergiyko SV, Katanyan GA, Veryaskina YA, Ivanov MK. Preoperative detection of malignancy in fine-needle aspiration cytology (FNAC) smears with indeterminate cytology (Bethesda III, IV) by a combined molecular classifier. J Clin Pathol. 2020;73(11):722-7. DOI: 10.1136/jclinpath-2020-206445. PMID: 32213552. Honglei G, Shahbaz M, Farhaj Z, Ijaz M, Kai SY, Davrieux CF, Cheng SZ. Ultrasound guided microwave ablation of thyroid nodular goiter and cystadenoma: A single center, large cohort study. Medicine (Baltimore). 2021;100(34):e26943. DOI: 10.1097/MD.0000000000026943. PMID: 34449459. Badrinarayanan V, Kendall A, Cipolla R. SegNet: A Deep Convolutional Encoder-Decoder Architecture for Image Segmentation. IEEE Trans Pattern Anal Mach Intell. 2017;39(12):2481-95. DOI: 10.1109/TPAMI.2016.2644615. PMID: 28060704. Hegedüs L, Frasoldati A, Negro R, Papini E. European Thyroid Association Survey on Use of Minimally Invasive Techniques for Thyroid Nodules. Eur Thyroid J. 2020;9(4):194-204. DOI: 10.1159/000506513. PMID: 32903971. Teti C, Panciroli M, Nazzari E, Pesce G, Mariotti S, Olivieri A, Bagnasco M. Iodoprophylaxis and thyroid autoimmunity: an update. Immunol Res. 2021;69(2):129-38. DOI: 10.1007/s12026-021-09192-6. PMID: 33914231. Yazıcıoglu MO, Yılmaz A, Kocaoz S, Ozcaglayan R, Parlak O. Risks and prediction of postoperative hypoparathyroidism due to thyroid surgery. Sci Rep. 2021;11(1):11876. DOI: 10.1038/s41598-021-91277-1. PMID: 34088943. D'Andrilli A, Venuta F, Rendina EA. Subglottic tracheal stenosis. J Thorac Dis. 2016;8(Suppl_2):S140-7. DOI: 10.3978/j.issn.2072-1439.2016.02.03. PMID: 26981264. Brinch FA, Dossing H, Nguyen N, Bonnema SJ, Hegedus L, Godballe C, Sorensen JR. The Impact of Esophageal Compression on Goiter Symptoms before and after Thyroid Surgery. Eur Thyroid J. 2019;8(1):16-23. DOI: 10.1159/000493542. PMID: 30800637. Czarnywojtek A, Zgorzalewicz-Stachowiak M, Czarnocka B, Sawicka-Gutaj N, Gut P, Krela-Kazmierczak I, Ruchala M. Effect of lithium carbonate on the function of the thyroid gland: mechanism of action and clinical implications. J Physiol Pharmacol. 2020;71(2). DOI: 10.26402/jpp.2020.2.03. PMID: 32633237. Murgu SD, Egressy K, Laxmanan B, Doblare G, Ortiz-Comino R, Hogarth DK. Central Airway Obstruction: Benign Strictures, Tracheobronchomalacia, and Malignancy-related Obstruction. Chest. 2016;150(2):426-41. DOI: 10.1016/j.chest.2016.02.001. PMID: 26874192. Ozgul MA, Gul S, Cetinkaya E, Turan D, Kırkıl G, Ugur Chousein EG, et al. Our eight years experience in postintubation/posttracheostomy tracheal stenosis. Tuberk Toraks. 2019;67(1):55-62. DOI: 10.5578/tt.68188. PMID: 31130136. Wright CD. Nonoperative Endoscopic Management of Benign Tracheobronchial Disorders. Thorac Surg Clin. 2018;28(2):243-7. DOI: 10.1016/j.thorsurg.2018.01.009. PMID: 29627058. Marcus A, Narula N, Kamel MK, Koizumi J, Port JL, Stiles B, et al. Sensitivity and specificity of fine needle aspiration for the diagnosis of mediastinal lesions. Ann Diagn Pathol. 2019;39:69-73. DOI: 10.1016/j.anndiagpath.2019.02.011. PMID: 30797131. Cho W, Sim JS, Jung SL. Ultrasound-guided ethanol ablation for cystic thyroid nodules: effectiveness of small amounts of ethanol in a single session. Ultrasonography. 2021;40(3):417-27. DOI: 10.14366/usg.20170. PMID: 33721967. Barczynski M, Stopa-Barczynska M. Hemithyroidectomy for benign euthyroid asymmetric nodular goitre. Best Pract Res Clin Endocrinol Metab. 2019;33(4):101288. DOI: 10.1016/j.beem.2019.06.004. PMID: 31281088. Iriarte MB, Morales EI, Velasquez M, Zuniga V, Sua LF, Fernandez-Trujillo L. Giant Intrathoracic Goiter of Atypical Presentation: A Case Report. Clin Pathol. 2020;13:2632010X20916741. DOI: 10.1177/2632010X20916741. PMID: 32363342. Freitas C, Martins N, Novais-Bastos H, Morais A, Fernandes G, Magalhaes A. The role of interventional bronchoscopy in the management of post-intubation tracheal stenosis: A 20-year experience. Pulmonology. 2021;27(4):296-304. DOI: 10.1016/j.pulmoe.2019.12.004. PMID: 31901372. Dellatore P, Bhagat V, Kahaleh M. Endoscopic full thickness resection versus submucosal tunneling endoscopic resection for removal of submucosal tumors: a review article. Transl Gastroenterol Hepatol. 2019;4:45. DOI: 10.21037/tgh.2019.05.03. PMID: 31304422. Osho A, Sachdeva U, Wright C, Muniappan A. Surgical management of tracheoesophageal fistula. Ann Cardiothorac Surg. 2018;7(2):314-6. DOI: 10.21037/acs.2018.03.06. PMID: 29707512. Kobaly K, Kim CS, Mandel SJ. Contemporary Management of Thyroid Nodules. Annu Rev Med. 2022;73:517-28. DOI: 10.1146/annurev-med-042220-015032. PMID: 34416120. Alexander LF, Patel NJ, Caserta MP, Robbin ML. Thyroid Ultrasound: Diffuse and Nodular Disease. Radiol Clin North Am. 2020;58(6):1041-57. DOI: 10.1016/j.rcl.2020.07.003. PMID: 33040847. Cataneo AJM, Felisberto G Jr, Cataneo DC. Thymectomy in nonthymomatous myasthenia gravis – systematic review and meta-analysis. Orphanet J Rare Dis. 2018;13(1):99. DOI: 10.1186/s13023-018-0837-z. PMID: 29940999. Holzer K, Bartsch DK. Struma nodosa [Nodular goiter]. Chirurg. 2020;91(9):712-9. DOI: 10.1007/s00104-020-01218-3. PMID: 32548696. [In German]. Yan L, Li X, Xiao J, Li Y, Zhu Y, He H, Luo Y. Contrast-enhanced ultrasound is a reliable and reproducible assessment of necrotic ablated volume after radiofrequency ablation for benign thyroid nodules: a retrospective study. Int J Hyperthermia. 2022;39(1):40-7. DOI: 10.1080/02656736.2021.1991009. PMID: 34936850. Mallick S, Jain S, Ramteke P. Pediatric mediastinal lymphoma. Mediastinum. 2020;4:22. DOI: 10.21037/med-20-37. PMID: 35118290. Myasthenic crisis demanding mechanical ventilation: A multicenter analysis of 250 cases. Neurology. 2020;94(16):724. DOI: 10.1212/WNL.0000000000009262. Erratum for: Neurology. 2020;94(3):e299-313. DOI: 10.1212/WNL.0000000000008688. PMID: 32269110. Hadedeya D, Kay J, Attia A, Omar M, Shalaby M, Youssef MR, et al. Effect of postsurgical chronic hypoparathyroidism on morbidity and mortality: a systematic review and meta-analysis. Gland Surg. 2021;10(10):3007-19. DOI: 10.21037/gs-21-181. PMID: 34804887. Livhits MJ, Zhu CY, Kuo EJ, Nguyen DT, Kim J, Tseng CH, et al. Effectiveness of Molecular Testing Techniques for Diagnosis of Indeterminate Thyroid Nodules: A Randomized Clinical Trial. JAMA Oncol. 2021;7(1):70-7. DOI: 10.1001/jamaoncol.2020.5935. PMID: 33300952. Bibas BJ, Cardoso PFG, Minamoto H, Pego-Fernandes PM. Surgery for intrathoracic tracheoesophageal and bronchoesophageal fistula. Ann Transl Med. 2018;6(11):210. DOI: 10.21037/atm.2018.05.25. PMID: 30023373. Moffatt DC, Tucker J, Goldenberg D. Management of compression symptoms of thyroid goiters: Hemithyroidectomy is equally as successful as total thyroidectomy. Am J Otolaryngol. 2023;44(1):103676. DOI: 10.1016/j.amjoto.2022.103676. PMID: 36279829. Nakamura T, Fujikawa R, Otsuki Y, Funai K. Prone position surgery for a subcarinal bronchogenic cyst. Surg Case Rep. 2018;4(1):151. DOI: 10.1186/s40792-018-0557-6. PMID: 30594978. Barbosa TLM, Junior COM, Graf H, Cavalvanti T, Trippia MA, da Silveira Ugino RT, et al. ACR TI-RADS and ATA US scores are helpful for the management of thyroid nodules with indeterminate cytology. BMC Endocr Disord. 2019;19(1):112. DOI: 10.1186/s12902-019-0429-5. PMID: 31664992. Dalar L, Karasulu L, Abul Y, Ozdemir C, Sokucu SN, Tarhan M, Altin S. Bronchoscopic Treatment in the Management of Benign Tracheal Stenosis: Choices for Simple and Complex Tracheal Stenosis. Ann Thorac Surg. 2016;101(4):1310-7. DOI: 10.1016/j.athoracsur.2015.10.005. PMID: 26704411. Jonklaas J, Bianco AC, Cappola AR, Celi FS, Fliers E, Heuer H, et al. Evidence-Based Use of Levothyroxine/Liothyronine Combinations in Treating Hypothyroidism: A Consensus Document. Thyroid. 2021;31(2):156-82. DOI: 10.1089/thy.2020.0720. PMID: 33276704. Derwahl KM. Medikamentöse Therapie des Schilddrüsenknotens [Medical Treatment of Thyroid Nodule]. Laryngorhinootologie. 2018;97(2):89-91. DOI: 10.1055/s-0043-124607. PMID: 29401546. [In German]. Aydogmus U, Kis A, Ugurlu E, Ozturk G. Superior Strategy in Benign Tracheal Stenosis Treatment: Surgery or Endoscopy? Thorac Cardiovasc Surg. 2021;69(8):756-63. DOI: 10.1055/s-0040-1715435. PMID: 32886930. Astl J, Plzak J, Lastuvka P, Betka J. Morbidity and mortality associated with thyroid surgery – retrospective analysis 19912010. Rozhl Chir. 2021;100(3):118-25. DOI: 10.33699/PIS.2021.100.3.118-125. PMID: 33910357. Jung W, Kang CH, Kim YT, Park IK. Primary Intrapulmonary Thymoma Presenting as a Solitary Pulmonary Nodule. Korean J Thorac Cardiovasc Surg. 2017;50(1):54-8. DOI: 10.5090/kjtcs.2017.50.1.54. PMID: 28180106. Horwich P, Chang BA, Asarkar AA, Randolph GW, Nathan CO. What Is the Role of Radiofrequency Ablation for Benign Thyroid Nodules? Laryngoscope. 2022;132(1):1-2. DOI: 10.1002/lary.29498. PMID: 33656181. Baloch Z, LiVolsi VA. The Bethesda System for Reporting Thyroid Cytology (TBSRTC): From look-backs to look-ahead. Diagn Cytopathol. 2020;48(10):862-6. DOI: 10.1002/dc.24385. PMID: 31999070.